21st Century Learning Design for Educators to Improve the Competence of Technology Literacy - Harahap, Erwin; Gunawan, Gani; Suhaedi, Didi; Ramdani, Yani; Suparman, Anan; Zein, Syahrul (KnE Social Sciences, 2023)
Technology literacy is a competency that cannot be avoided by educators, especially during the current Covid-19 pandemic. They are required to possess and improve their technological skills to support the learning process, especially as face-to-face implementation is not possible. However, many educators face difficulty and have not mastered technology in the field of learning, particularly various technology applications connected to the Internet, which facilitate remote or online learning. To address these challenges, the community service team from the Mathematics department at Universitas Islam Bandung took the initiative to organize education and training activities as a solution to improve educators’ technological literacy competence. One of the most suitable learning methods applied during this pandemic is the 21st Century Learning Design (21CLD) packaged in a Microsoft Certified Educator (MCE) certification program. Through this MCE training activity, it is hoped that educators can enhance their technological literacy competencies and apply them in their respective educational institutions along with their students. The MCE training activities were conducted for 8 days, starting from May 26, 2022, to June 20, 2022, every Monday and Thursday, from 15.00 to 18.00 online via Zoom conference apps. The training was attended by educators from MTs and SMK at Tarogong District, City of Garut, Indonesia. Keywords: microsoft certified educator, 21CLD, century, learning, design, sertification